Theoretical, Psychological, and Philosophical Interrelation in Mathematics Learning through YouTube for Elementary School Students - Sri Hartatik; Nafiah Nafiah; Pance Mariati (STAI Hubbulwathan Duri, 2023)
Modern education integrates several aspects as a single unit of learning, especially for elementary school students. This study identifies the interrelation of art, technology, education, and mathematics for elementary school students. A new style of education that incorporates both the arts and the sciences is also considered in this research: interactive learning. Using netnography, this investigation takes a multi-site qualitative approach. Furthermore, the study was conducted by conducting netnographic observations on the YouTube channel with the keyword